ESTIMATE OF WOOD VOLUME DEPARTING FROM THE DIAMETER AT STUMP HEIGHT IN AN EXPLOITED AREA IN “TERRA FIRME” AMAZON FOREST - Leite, Flávia Saltini (2010)
This research aimed to estimate the volume of trees of a “terra-firme” tropical forest, considering only the diameter at stump height (d0), as independent variable. The area being studied is located in Breu Branco, Pará. A total of 113 trees with DBH ≥ 51 cm, of different species and diameter classes, were selected to determine the observed cubic volume of the commercial trunk. The trees were rigorously cubed by the method of Hohenadl considering the division of the commercial trunk in ten sections of equals lengths, and the volume of each section of the trunk was determined by the Smalian formula. Equations were adjusted to estimate the commercial volume of the trees in function of d0 and in function of DBH, for comparisons. Results showed that d0 had a high correlation with the commercial volume of trees within the area of forest of “terra firme” and it can be used for the adjustment of mathematical models in order to estimate the commercial volume of trees. No significant difference between the observed and the estimated volume of trees – generated by the adjusted linear equation in function of d0 – was found.